2013
DOI: 10.1371/journal.pone.0077942
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ceruloplasmin Levels Correlate Negatively with Liver Fibrosis in Males with Chronic Hepatitis B: A New Noninvasive Model for Predicting Liver Fibrosis in HBV-Related Liver Disease

Abstract: AimsThis study aimed to investigate associations between ceruloplasmin (CP) levels, inflammation grade and fibrosis stages in patients with chronic hepatitis B (CHB) and to establish a noninvasive model to predict cirrhosis.MethodsLiver biopsy samples and sera were collected from 198 CHB patients randomized into a training group (n=109) and a validation group (n=89). CP levels were determined using nephelometric immunoassays. Relationships between CP and liver inflammation and fibrosis were analyzed by Spearma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…We previously developed a new non-invasive model of APPCI to predict liver cirrhosis in CHB patients presenting different ALT levels and found that serum CP was a new marker, negatively correlated with liver fibrosis[25]. In the present study, we extended these results to CHB carriers with normal or minimally raised ALT.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…We previously developed a new non-invasive model of APPCI to predict liver cirrhosis in CHB patients presenting different ALT levels and found that serum CP was a new marker, negatively correlated with liver fibrosis[25]. In the present study, we extended these results to CHB carriers with normal or minimally raised ALT.…”
Section: Discussionsupporting
confidence: 53%
“…Whether they are also applicable to CHB patients, however, is yet to be demonstrated. Therefore, new non-invasive models were recently developed to detect liver fibrosis in patients with CHB[19,25,45,46]. Compared with FIB-4 and GP, our CG model showed much greater AUC than FIB-4 to the GP model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations